Impact of rock content and fine-grained soil properties on the compressive deformation behavior of soil-rock mixtures - Gong, Jian; Wang, Jianfeng; Zhang, Shiting; Xing, Yuxing; Deng, Liangbin; Long, Zhengliang; Pang, Xianwei; Jiang, Mingjie (Frontiers in Earth Science, 2025)
Soil-rock mixtures are extensively used in geotechnical engineering applications, such as embankment construction, dam engineering, and slope reinforcement, where their compressive deformation characteristics play a crucial role in influencing the stability and settlement behavior of these structures. This study investigates how variations in rock content (W), effective stress (σv) and fine-grained soil properties (quartz sand and silty red clay) affect the one-dimensional compression behavior of soil-rock mixtures. Key compression parameters, including the compression index Cc and the secondary compression index Ca, were obtained and analyzed through one-dimensional consolidation tests to assess the deformation characteristics of these mixtures. Results show that under the same effective stress (σv), both the Cc and Ca exhibit different trends with W, depending on the properties of the fine-grained soil. Soil-rock mixtures with silty red clay demonstrate more pronounced secondary consolidation effects at low rock content, whereas mixtures with quartz sand display weaker secondary consolidation overall. The significantly lower Ca/Cc values in the quartz sand mixtures suggest that secondary settlement is much smaller in these mixtures compared to those containing silty red clay.